EFFECTS OF ISCHEMIC PRECONDITIONING ON HIGH INTENSITY INTERVAL PERFORMANCE AND RECOVERY ON BADMINTON PLAYERS - Veli Volkan Gürses; Mustafa Kerem; Mustafa Şakir Akgül; Bayram Ceylan; Bilgehan Baydil (ümit doğan üstün, 2018)
The aim of this study was to examine the effect of ischemic preconditioning (IPC) on high intensity interval training and recovery parameters on badminton players. Sixteen well trained badminton players (male n= 10, female n=6 age: 18.90 ± 0.99, 20.33 ± 1.75 years; height: 176.50 ± 5.42, 159.33 ± 3.61 cm; body weight: 72.55 ± 7.93, 54.93 ± 4.53 kg; systolic blood pressure: 12.30 ± 1.15, 11.16 ± 1.47 mmHg; diastolic blood pressure: 7.80 ± 1.22, 7.66 ± 0.81 mmHg) voluntarily participated in the study. All participant were able to complete all trails. A randomized crossover study design was performed to investigate the acute effect of IPC on high intensity interval training performance and recovery. The Wingate Style high intensity interval training (HIIT) workout was conducted as generate to physiological fatigue. The HIIT protocol was involved 30 seconds of "all-out" cycling 3 times with 4 minutes rest against a high resistance which participants 7.5% of body weight. Relative Peak Power (PP), Relative Mean Power (MP) and Power Drop (PD%) were evaluated for every repeated trails to execute HITT performance. Rested; hearth rate (HR), blood lactate concentration (BLAC) and blood pressure (BP) values were evaluated. HR, BLAC and BP values were measured after, 12 and 30 minute after exhaustion. IPC were conducted 3 set × 5 min 220 mmHg. 72 hours rest was given between measurements. Nonparametric Wilcoxon Sign Rank Test used to determine the effect of IPC on performance and recovery parameters. All data were processed at the significance level p.05). The impact of IPC were -6.5%, -5.8% and 24.5% were respectively. According to these results it is assumed that IPC applications seems to be not effective method as enhancing performance in badminton players.